Pengaruh Penggunaan Media Sosial Terhadap Disaster Awareness di MAN Wonogiri - Chamidawati, Triningtyas; Utomo, Aji Wahyu; Melani, Grestina; Bakar, Abdullah; Dewi, Ratih Puspita; Widiyatmoko, Wahyu (Universitas Muhammadiyah Surakarta, 2025)
In this digital era, social media has become an integral part of daily life. Its use is highly diverse, one of which is as a medium for disseminating disaster-relate information. This study aims to examine: 1) the level of social media use, 2) the level of disaster awareness, 3) the influence of social on natural disaster awareness of MAN Wonogiri students. This research employed a quantitative approach with a correlational research design. The study population consisted of 556 students, from which a sample of 233 students was selected using the slovin formula with a significance level of 5%. The sampling techinique applied was simple random sampling. Data were collected using a questinnaire, and the analysis involved scoring and statistical testing using the spearman rank correlation. The results of the study indicated that: (1) the level of social media use had an average score of 23.4 (90.5%), which was classified in the moderate category, (2) the level of natural disaster awareness had an average score of 105 (94.6%), which was categorized as high, and (3) the inferential test result showed a significance value of 0.02 (< 0.05), based on these findings, it was concluded that social media use did not affect the level of natural disaster awareness among MAN Wonogiri students.